Bio-processing of algal bio-refinery: a review on current advances and future perspectives - Koyande, Apurav Krishna; Show, Pau-Loke; Guo, Ruixin; Tang, Bencan; Ogino, Chiaki; Chang, Jo-Shu (Taylor and Francis Inc., 2019)
Microalgae biomass contains various useful bio-active components. Microalgae derived biodiesel has been researched for almost two decades. However, sole biodiesel extraction from microalgae is time-consuming and is not economically feasible due to competitive fossil fuel prices. Microalgae also contains proteins and carbohydrates in abundance. Microalgae are likewise utilized to extract high-value products such as pigments, anti-oxidants and long-chain polyunsaturated fatty acids which are useful in cosmetic, pharmaceutical and nutraceutical industry. These compounds can be extracted simultaneously or sequentially after biodiesel extraction to reduce the total expenditure involved in the process. This approach of bio-refinery is necessary to promote microalgae in the commercial market. Researchers have been keen on utilizing the bio-refinery approach to exploit the valuable components encased by microalgae. Apart from all the beneficial components housed by microalgae, they also help in reducing the anthropogenic CO2 levels of the atmosphere while utilizing saline or wastewater. These benefits enable microalgae as a potential source for bio-refinery approach. Although life-cycle analysis and economic assessment do not favor the use of microalgae biomass feedstock to produce biofuel and co-products with the existing techniques, this review still aims to highlight the beneficial components of microalgae and their importance to humans. In addition, this article also focuses on current and future aspects of improving the feasibility of bio-processing for microalgae bio-refinery.